An evaluation of two distributed deployment algorithms for Mobile Wireless Sensor Networks - Aguilera, Francisco; Urdiales-García, Amalia Cristina; Sandoval-Hernández, Francisco (My University, 2015)
Deployment is important in large wireless sensor networks (WSN), specially because nodes may fall due to failure or battery issues. Mobile WSN cope with deployment and reconfiguration at the same time: nodes may move autonomously: i) to achieve a good area coverage; and ii) to distribute as homogeneously as possible. Optimal distribution is computationally expensive and implies high tra c load, so local, distributed approaches may be preferable. This paper presents an experimental evaluation of role-based and behavior based ones. Results show that the later are better, specially for a large number of nodes in areas with obstacles.
Keywords: Comunicación -- Análisis de red; Mesh mobile sensor networks; WSN; SPF; BDM; Deployment